PENENTUAN BATAS MINIMUM PARAMETER VISIBILITAS HILAL SAAT SUMMER SOLSTICE DAN WINTER SOLSTICE - Musfiroh, Imas (ELFALAKY: Jurnal Ilmu Falak, 2018)
Crescent visibility importantly depends on some variables such as; Sun-Crescent elongation (ArcL, arc of light), Crescent relative altitude due to Sun (ArcV, arc of vision), moon age, and moon lag (briefly Lag only). Furthermore, relative position of Sun due to ecliptic can affects Crescent position and its visibility. There is two significantly relative position of Sun i.e. Summer Solstice which happens on June 21-22, and Winter Solstice which occurs on December 21-22. In this paper, it will be discussed about what is minimum limit of Crescent visibility on those phenomena. Writer used data from 68 BMKG data (2008-2015), 295 Yallop data (1861-1992), and 36 Caldwell data (1987-2012), but they are used when Summer and Winter Solstice only. It can be concluded that the minimum limit of Crescent visibility are, ArcL = 10°30’00”, ArcV = 9°30’00”, moon age 20 hours 24 minutes, lag 58 minutes 48 seconds and Crescent width 0,24 arcminutes on June 26, 1987 at latitude 42°42’00” South and longitude 84°30’00” West, occured 4 days after Summer solstice.